2022
DOI: 10.1177/03000605221084881
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae invasion syndrome: a case of liver abscess combined with lung abscess, endophthalmitis, and brain abscess

Abstract: Klebsiella pneumoniae invasion syndrome (KPIS) is a critical multi-site infection that is usually caused by highly virulent Klebsiella pneumonia. It is relatively common in Asian patients with diabetes and leads to sepsis, which has a high mortality rate. We report the case of a man in his early 40s who presented to the hospital with blurred vision in his left eye of 7 days’ duration and fever of 1 day’s duration. After a complete examination, he was diagnosed with KPIS on the basis of his liver abscessation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…It was consistent with previous reports. 3,8,[31][32][33][34] In our study, the pathogen identified was concordant in seven of 10 culture-positive cases. Discordance between mNGS and culture was also reported in the literature.…”
Section: Discussionsupporting
confidence: 62%
“…It was consistent with previous reports. 3,8,[31][32][33][34] In our study, the pathogen identified was concordant in seven of 10 culture-positive cases. Discordance between mNGS and culture was also reported in the literature.…”
Section: Discussionsupporting
confidence: 62%
“…Diabetes is considered a significant risk factor for IKPLAS, and up to 63% of patients with a bacterial liver abscess in Taiwan have diabetes. This may be related to the impaired phagocytosis of K1/K2 Klebsiella pneumoniae in diabetic patients [ 31 ] and the more excellent vascular permeability in diabetic patients, which is conducive to bacterial invasion [ 11 ]. The above two serotypes of Klebsiella pneumoniae are also highly virulent Klebsiella pneumoniae, which show high viscosity in the String test [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen from the SHAP plot, the higher the SOFA score, the greater the risk of progression to IKPLAS. Although the pathogenesis of IKPLAS is currently unclear, the study by Chen-Guang Zhang et al shows that most diabetic patients with IKPLAS are prone to sepsis [ 11 ]. Blood-borne transmission may be one of the more important ways.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Endophthalmitis caused by Klebsiella pneumoniae induced liver abscess (KP-PLA) was first reported in Taiwan in the 1980s, [ 2 ] and some rare complications of liver abscess such as brain abscess and lung abscess have been reported successively in recent years. [ 3 , 4 ] As medicine progressed, acute pancreatitis (AP) was characterized by bacterial infections, including salmonella and tuberculosis, in addition to the common causes such as Biliary tract disease, alcohol, and high triglycerides. [ 5 , 6 ] Klebsiella pneumoniae usually causes secondary infection after AP, there have been no cases of primary infectious pancreatitis caused by Klebsiella pneumoniae excluding other causes.…”
Section: Introductionmentioning
confidence: 99%